Effectiveness of Agricultural Knowledge Disseminated on Social Media - G. P. Sandeep; P. Prashanth; M. Sreenivasulu; A. Madhavilata (Journal of Agricultural Extension Management, 2021)
Knowledge is a primary invisible input in the agriculture production process. Knowledge helps farmers in deciding on a wide range of farm activities, i.e., selecting the crop for production to final selling the produce. The agriculture research and extension institutes constitute a significant source of agricultural knowledge and information. They are using all information dissemination methods to bridge the information gap among farmers. Social media platforms are dominating agricultural information dissemination platforms at the field level. The present study is conducted to study the effect of agricultural information on farmers’ knowledge levels. The Ex-post facto research design was adopted for the study with a sample of 120 respondents, covering all three erstwhile districts from the Southern Telangana Zone of Telangana state.